Path Dependency and Communal Tolerance in Indonesia - Gde Dwitya Arief Metera (Studies of Transition States and Societies, 2017)
Book review Menchik, Jeremy (2016). Islam and Democracy in Indonesia: Tolerance without Liberalism.